ฉากทัศน์ทางการเมืองไทยและจริยธรรมทางการเมือง - เชื้อวณิชย์, จิตรตรา; ไกรศรี, ธนภรณ์; จินดารัมย์, ณัฐพล (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
Political and administrative changes in Thailand. From a perspective of political development, this entails the establishment of a nation-state with a centralized government that governs the entire country and instills a sense of citizenship among the people. However, during this time, political power in Thailand was primarily concentrated in the hands of a group of high-ranking officials who were considered the elite. Non-bureaucratic political groups and ordinary citizens were not allowed to participate in politics, leading to a lack of political entities to control, monitor, or oppose political actions. Consequently, these Thai officials or political elites greatly benefited from acquiring, preserving, and exercising political power, often through means that were considered unjust or illegitimate. Historical evidence suggests that these political elites originally attained power through the use of force, and once in power, they showed little intention of transferring that power to the people. Thus, politics in Thailand during that era revolved around a select group of high-ranking military and civilian officials. In different eras of Thailand, elections have been held where political parties and candidates present their policies to attract public attention and secure electoral victories. This process resembles a competition to sell political products, employing various political communication techniques and marketing tactics. The ultimate goal is to garner support from the people. However, relying solely on legal provisions to control the political behavior of society's members can prove challenging. Similarly, the use of laws that govern general human behavior alone may not yield significant effects. Therefore, it becomes necessary to apply moral principles, including religious ethics, to exert control. The effectiveness of political behavior among society's members can be enhanced by political ethics, with moral courage serving as a virtue that promotes good democratic citizenship. Moral courage encompasses ideological commitment, political knowledge, a sense of political awareness, and an understanding of political emotions